A scanometric antibody probe for facile and sensitive immunoassays1. Issue 42 (25th May 2015) - Yi, So Yeon; Lee, UiJin; Chung, Bong Hyun; Jung, Juyeon
<x xml:space="preserve">Abstract</x> We have developed a novel scanometric antibody probe for rapid, sensitive, and naked-eye-visible immunoassays.